Análise de viabilidade econômica do método construtivo insulated concrete forms para construção de habitações - Bastos Junior, Achilles Pinheiro (Universidade Federal Rural do Semi-Árido, 2018)
The use of expanded polystyrene blocks or structures in civil construction is of European origin (Germany). It was developed for regions subject to earthquakes and low temperatures in the 1950s, with the intention of creating a simple, innovative, sustainable and low-cost structure that would not collapse and add thermal and acoustic elements to the built environment. Thus, with the advancement of construction materials technologies and concerns about economic uncertainty and supply, construction companies have opted for innovative materials and methods. The paper intends to present a case study in order to analyze the economical feasibility of the implementation of the construction system, with the objective to make a comparison with the conventional method. In this way, we intend to show in the present work that the Insulated Concret Forms construction system is feasible even though it has considerable differences in the conventional system, but the advantages and benefits extend in the long term.
Monografia
Keywords: ICF; Construção sustentável; Análise comparativa; Sistema construtivo; ICF; Sustainable construction; Comparative analysis; Construction system; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA